Specific enzymatic dephosphorylation of the retinoblastoma protein. - Ludlow, J W (1993)
The retinoblastoma gene product (RB) undergoes cell cycle-dependent phosphorylation and dephosphorylation. Pulse-chase experiments revealed that the change in RB gel electrophoretic migration which occurs near mitosis is due to enzymatic dephosphorylation (J. W. Ludlow, J. Shon, J. M. Pipas, D. M. Livingston, and J. A. DeCaprio, Cell 60:387-396, 1990). To determine the precise timing of RB dephosphorylation and whether a specific phosphatase is active in this process, we have utilized a nocodazole block and release protocol which allows a large population of cells to progress synchronously through mitosis. In such experiments, RB dephosphorylation began during anaphase and continued until complete dephosphorylation was apparent in the ensuing G1 period. In addition, late mitotic cell extracts were capable of dephosphorylating RB in vitro. This RB-specific mitotic phosphatase activity was more active in anaphase extracts than in pro- or metaphase extracts, which is consistent with the results obtained in vivo. Okadaic acid and protein phosphatase inhibitors 1 and 2 inhibited this specific RB phosphatase activity. These results suggest a role for serine and threonine phosphoprotein phosphatase type 1 in the late mitotic dephosphorylation of RB.